Merunut Bentuk Relik Leksikon Dasar Bahasa Jawa-Carita - M. Suryadi M. Suryadi (Program Studi Sastra Indonesia, Fakultas Ilmu Budaya, Universitas Diponegoro, 2017)
Carita Javanese (BJC) is one among other Javanese dialects. It stands as a dialect as well as Javanese enclave. The area of the speech community of BJC stretches in the most west of the Javanese speech community area and the middle of Sundanese speech community. In spite of the marginal site of the BJC speech community, it still preserves relic forms of old Javanese by still maintaining the forms and their meaning. The search for the relic forms of the BJC can be done through reconstruction method by making us of Proto Melayo-Javanese reconstruction, and referential comparative method carried on by resemblance comparative relation technique, and difference comparative relation technique against the main problems. The main refernce in use is the old Javanese dictionary and manuscripts. The analysis results in description about relics which are still preserved in BJC also completed with their heritage path.